Mekanisme Pertahanan Diri Pada Tokoh Lail Untuk Menghadapi Problematika Kehidupan Dalam Novel Hujan Karya Tere Liye - Titik Tri Dewi Ratnaningsih; Aufa Istiyaroh; Eva Dwi Kurniawan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to describe the self-defense mechanism taken from Sigmund Freud’s theory used by the main character in the literary work of the novel entitled Rain by Tere Liye. The problems studied are how the female main character in the novel faces the problems of her life and what forms of self-defense are used when the main character faces problems. The approach taken from this research uses a qualitative approach that focuses on the main character with the research method used, namely using a literary psychology approach. The results obtained show that the main female character in the novel uses forms of self-defense mechanisms in dealing with the problems of her life.